Development of medical writing in India: Past, present, and future - Suhasini Sharma (Perspectives in Clinical Research, 2017)
Pharmaceutical medical writing has grown significantly in India in the last couple of decades. It includes preparing regulatory, safety, and publication documents as well as educational and communication material related to health and health-care products. Medical writing requires medical understanding, knowledge of drug development and the regulatory and safety domains, understanding of research methodologies, and awareness of relevant regulations and guidelines. It also requires the ability to analyze, interpret, and present biomedical scientific data in the required format and good writing skills. Medical writing is the fourth most commonly outsourced clinical development activity, and its global demand has steadily increased due to rising cost pressures on the pharmaceutical industry. India has the unique advantages of a large workforce of science graduates and medical professionals trained in English and lower costs, which make it a suitable destination for outsourcing medical writing services. However, the current share of India in global medical writing business is very small. This industry in India faces some real challenges, such as the lack of depth and breadth in domain expertise, inadequate technical writing skills, high attrition rates, and paucity of standardized training programs as well as quality assessment tools. Focusing our time, attention, and resources to address these challenges will help the Indian medical writing industry gain its rightful share in the global medical writing business.